HUBUNGAN ANTARA ASUPAN ASAM LEMAK LINOLEAT DAN KADAR HEMOGLOBIN (Hb) DENGAN KEJADIAN DYSMENORRHEA PADA REMAJA PUTRI DI KELURAHAN TAMBAKAJI KECAMATAN NGALIYAN KOTA SEMARANG - Ika Sartika; Muflihah Isnawati; Setyo Prihatin; Mohammad Jaelani (JURNAL RISET GIZI, 2015)
Background : Dysmenorrhea is menstrual pain that arises before or during menstruation. The results of preliminary studies found that 70% of young women experience dysmenorrhea. Prostaglandin comes from arachidonic acid which is synthesized from linoleic fatty acids which function in the inflammatory response. In the case of anemia, the ability of hemoglobin to transport oxygen decreases, this will lead to more production of prostaglandin and trigger stronger uterine contractions.Objective : The purpose of this study was to determine the relationship between linoleic fatty acid intake and Hemoglobin (Hb) levels with the incidence of dysmenorrhea in young women.Method : This research is an analytical descriptive study in the field of clinical nutrition using a cross sectional design. The research subjects were 47 young women who had received menstruation. Data collection included 2x24 hour food recall to determine linoleic fatty acid intake and blood sampling to determine Hb levels. Variable analysis was carried out in the form of univariate and bivariate. Bivariate test uses fisher exact test.Results : 63.8% of respondents had more intake of linoleic fatty acids so that they were at risk of inflammation. 44.7% of respondents suffer from anemia. Respondents who had moderate dysmenorrhea were 66%. Respondents with more fat intake and moderate dysmenorrhea were 70% (p value = 0.029). Respondents suffering from anemia and experiencing moderate dysmenorrhea were 85.7% (p value = 0.012).Conclusion : Linoleic fatty acid intake and Hb levels were associated with the incidence of dysmenorrhea in young women.